2022
DOI: 10.1186/s12888-022-03839-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between depressive symptoms and poor sleep quality among pregnant women in Northern Rural Bangladesh: a community-based cross-sectional study

Abstract: Background Adequate good quality of sleep is essential for physical fitness during pregnancy as well as being a depressive symptoms-free mind. However, there is little evidence of the relationship between depressive symptoms and poor sleep quality among pregnant women in Bangladesh. This study aimed to find the association between depressive symptoms and poor sleep quality among pregnant women in northern rural Bangladesh. Methods A community-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
1
4
0
1
Order By: Relevance
“…The analysis found that loneliness could positively correlate with mental distress, suggesting that individuals who feel lonely are more likely to experience mental distress. This finding supports previous observations 32 , 59 . Social isolation adversely affects mental health in many ways.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The analysis found that loneliness could positively correlate with mental distress, suggesting that individuals who feel lonely are more likely to experience mental distress. This finding supports previous observations 32 , 59 . Social isolation adversely affects mental health in many ways.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, two systematic reviews of nine and 51 studies each concluded that mental health problems such as depression and anxiety increase sleep disturbance 28,29 . In turn, loneliness and mental distress have been shown in multiple crosssectional and longitudinal studies to be associated with an increased risk of poor sleep, although the relationship could be bidirectional [30][31][32] . Thus, there is a possibility that poor sleep quality may lead to loneliness and social isolation, particularly in later life.…”
mentioning
confidence: 99%
“…As of second gestational trimester, complaints related to sleep increase: orthopnea, inguinal pain, cramps, uncomfortable position, urinary urgency, nightmares, and unsatisfactory night rest are the main ones. In the third trimester, there is a worsening of complaints compared to other gestational periods (19) .…”
Section: Discussionmentioning
confidence: 97%
“…A partir do segundo trimestre gestacional, as queixas relacionadas ao sono aumentam: ortopneia, dor inguinal, cólicas, posição desconfortável, urgência urinária, pesadelos e repouso noturno insatisfatório são as principais. No terceiro trimestre, há piora das queixas em relação a outros períodos gestacionais (19) .…”
Section: Variávelunclassified